Congo no peace without women an interview with Denis Mukwege. (Journal of International Affairs, 2013)
“On September 2012, a Congolese doctor stood before the world’s leaders at the United Nations General Assembly and denounced the mass rapes of women and girls in the Democratic Republic of Congo (DRC), and the impunity enjoyed by the responsible. Dr. Mukwege said he was ashamed of the international community’s failure to stop these atrocities. A month later, he was attacked in his residence in Bakavu, DRC, and was forced into exile. Dr. Mukwege, was nominated for the Nobel Peace Prize in 2012 and in 2013, returned to the Congo earlier this year in January to resume his work at the Panzi Hospital. There, he treats victims of sexual violence in a country ripped apart by sixteen years of conflict. According to the UN, “Sexual violence in the Congo is the worst in the world.” Around 500,000 women have been raped in the country since 1996. Dr. Mukwege shared his insights with the Journal about the Congolese crisis and the role of women in conflict.”